Facilitation of antagonist motor output through short-latency sensory pathways during postnatal development in the mouse. (1st May 2018) - Sonner, Patrick M.; Ladle, David R.
Highlights: Reciprocal inhibition classically leads to inhibition of antagonist motor neurons. Proprioceptive afferents can also evoke excitation in antagonist motor neurons. Facilitation occurs at latencies consistent with a disynaptic circuit. Facilitation is restricted to antagonist muscle pairs. Abstract: Reciprocal inhibition of motor neurons via Ia inhibitory interneurons recruited by stimulation of proprioceptive afferents supplying antagonist muscles has been well described. Changes in the efficacy of inhibition, and sometimes even a switch from inhibition to facilitation, have been reported in the literature after disruption of descending pathways. We sought to test whether such facilitation could be expressed in normal animals by evaluating the presence of facilitation in acute preparations from uninjured animals. Using an isolated spinal cord preparation from neonatal mice, changes in the monosynaptic stretch reflex response in knee flexor motor neurons (posterior biceps semitendinosus; PBST) were monitored following conditioning stimulation of proprioceptive sensory afferents in other muscle nerves. As expected for reciprocal inhibition, conditioning by stimulation of quadriceps (knee extensors and PBST antagonists) sensory afferents resulted in inhibition of the stretch reflex response. Facilitation, however, of the stretch reflex response by quadriceps conditioning stimulation was observed when the glycinergic reciprocal inhibitory pathway was blocked by application of strychnine. Facilitation was elicited by low-threshold proprioceptive afferents and occurred at latencies consistent with a disynaptic circuit. The magnitude of facilitation was larger at birth than at one week postnatal. Our results also suggest reciprocal facilitation is restricted to antagonist muscle pairs, as facilitation of PBST responses was not observed when conditioned with the obturator nerve supplying the adductor muscles. Overall, these data suggest the efficacy of facilitation is modulated during the first postnatal week, while the specificity of facilitation is already established by birth.